2018
DOI: 10.1038/s41598-018-21993-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrofusion of single cells in picoliter droplets

Abstract: We present a microfluidic chip that enables electrofusion of cells in microdroplets, with exchange of nuclear components. It is shown, to our knowledge for the first time, electrofusion of two HL60 cells, inside a microdroplet. This is the crucial intermediate step for controlled hybridoma formation where a B cell is electrofused with a myeloma cell. We use a microfluidic device consisting of a microchannel structure in PDMS bonded to a glass substrate through which droplets with two differently stained HL60 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…As an alternative method, a droplet-based microfluidic system can also be created for a high-throughput hybridoma production platform, including cell encapsulation, droplet pairing, droplet fusion and droplet shrinkage, then the cells form intimate contact for subsequent electrical fusion (R. M. Schoeman, Kemna, Wolbers, & van den Berg, 2014), as shown in Figure 4B. The results confirmed that the fusion rate of around 5%, droplet electrofusion was a promising cell fusion platform (Rogier M. Schoeman et al, 2018).…”
Section: Cell Electrofusion Within Microfluidic Devicesmentioning
confidence: 66%
“…As an alternative method, a droplet-based microfluidic system can also be created for a high-throughput hybridoma production platform, including cell encapsulation, droplet pairing, droplet fusion and droplet shrinkage, then the cells form intimate contact for subsequent electrical fusion (R. M. Schoeman, Kemna, Wolbers, & van den Berg, 2014), as shown in Figure 4B. The results confirmed that the fusion rate of around 5%, droplet electrofusion was a promising cell fusion platform (Rogier M. Schoeman et al, 2018).…”
Section: Cell Electrofusion Within Microfluidic Devicesmentioning
confidence: 66%
“…4B) . The micro channels were also yin-yang-shaped and produced droplets with a volume of 50 pL [26] . The obvious difference from the previous study is that the number of electrodes increased from one to six.…”
Section: Microdroplet Electrofusion Chipmentioning
confidence: 99%
“…An advantage of this technique over microwells is the speed of droplet generation and the ease of automation, which allows high-throughput assembly of cell aggregates (Allazetta and Lutolf, 2015;Chan et al, 2013;Tumarkin et al, 2011). In contrast to microwells, which rely on probabilistic cell loading, recent advances in droplet-based microfluidics can achieve singlecell droplet loading and can load droplets with combinations of cell types with a precision that exceeds Poisson limitations (Collins et al, 2015;Edd et al, 2008;Schoeman et al, 2014). These devices can also be used to capture precise cell pairs, facilitating the dynamic dissection of cell-cell interactions from the initiation of contact (Dura et al, 2016).…”
Section: Microfluidics Approaches Guide Organoid Size and Shapementioning
confidence: 99%